O ritual sagrado: a religião indígena do povo Xukuru do Ororubá (Pesqueira e Poção-PE). - Melo, Constantino José Bezerra de (2019)
In this study, we seek to understand the construction of the Indigenous Religion of the Sacred Ritual in the Terreiros of the Xukuru people of Ororubá (Pesqueira and Poção/PE) with the resumption and re-enchantment of the Terreiros of Serra do Ororubá. The research was based on the epistemological assumptions of the Sciences of Religion, in the interdisciplinary dialogue with other areas of knowledge to analyze the socio-historical and anthropological processes of the construction of the indigenous religion. We chose the categories ethnic emergency and territorialization in the approach of Social Anthropology to problematize the concept “Indians of the Northeast” and the religion concept of the Sciences of Religion as a human construct to analyze the formatting of the Indigenous Religion expressed by the Xukuru of the Ororubá indians, understanding how this religion was managed and is configured in the present. We analyze the construction of religious identity with its approaches and relations with other religious symbolic systems, through the concept of cultural identity and hybridization used in Anthropology, as well as the concept of Brazilian matrix religion, taking into account the possibilities of double or multiple religious belongings among the participants in the religion of the Sacre Ritual of the Xukuru Indians of the Ororubá. In the field research, we adopted the ethnographic method, having as instruments to collect data and information participant observation and interviews with open and semi-structured questions. Eighteen indigenous people were interviewed, practicing the activities of pajé, bacurau, gaiteiro, médiuns and leaders in the Terreiro of the Sacred Ritual. With this methodology, we seek to understand the reconstruction of individual and collective memories about the Religion of the Sacred Ritual. As a result of this research, we hope to contribute to the discussions and understanding of how the Xukuru Indians of Ororuba elaborated the construction of their Indigenous Religion in the format of the Sacred Ritual with the resumption and re-enchantment of the Terreiros in the Serra do Ororubá, mobilizing a process of religious and politics on the frontiers of dialogue with the other religious experiences of other symbolic systems in the indigenous teritory.